Analisis Optimalisasi Kompetensi Sumber Daya Manusia Pengadaan Barang dan Jasa Pemerintah - Jalma, Hazid (Prosiding, 2024)
Procurement of Goods and Services (PGS) is a procurement activity by Ministries, Institutions, Regional Apparatus financed by the APBN or APBD whose process starts from identifying needs, to handing over the results of the work. It is hoped that PGS can take place more effectively and efficiently and prioritize the application of the principles of healthy, transparent, open and fair business competition for all parties and of course can be accounted for. Every year the Central Government and Regional Governments make annual financial plans which are outlined in the APBN and APBD where the spending budget, especially PGS, continues to increase. The implementation of PGS, which is held every year and planned continuously, is not free from problems that continue to grow. This is based on the competence of human resources (HR) which does not yet reflect the implementation of Good Governance. HR competency problems occur in almost all regions in Indonesia. Government PGS is essentially an effort by the government to obtain the desired goods and services by using methods and processes in accordance with the provisions in order to reach an agreement regarding the price, time and quality of goods and services. Government PGS is essentially an effort by the government to obtain the desired goods and services by using methods and processes in accordance with the provisions in order to reach an agreement regarding the price, time and quality of goods and services. Therefore, optimizing the competency of government PGS human resources is the key to achieving efficient and effective procurement goals. By improving the quality of human resources through expertise and knowledge, improving the reward and sanction system, we can improve the effective and efficient implementation of the government's PGS